2022
DOI: 10.1002/jcp.30772
|View full text |Cite
|
Sign up to set email alerts
|

The Clock‐NAD+‐Sirtuin connection in nonalcoholic fatty liver disease

Abstract: Nonalcoholic or metabolic associated fatty liver disease (NAFLD/MAFLD) is a hepatic reflection of metabolic derangements characterized by excess fat deposition in the hepatocytes. Identifying metabolic regulatory nodes in fatty liver pathology is essential for effective drug targeting. Fatty liver is often associated with circadian rhythm disturbances accompanied with alterations in physical and feeding activities. In this regard, both sirtuins and clock machinery genes have emerged as critical metabolic regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…One gene, DUSP1, is a major negative regulator of MAP kinase signaling that is decreased in MASLD patients and shows increased expression following gastrectomy linked to the amelioration of liver disease [94]. The second gene, SIRT1, protects cells from metabolic stress and steatotic liver disease by deacetylating proteins associated with lipid metabolism [95, 96]. A third inhibited late upstream regulator, CITED2, is a transcriptional co-activator that promotes hepatic gluconeogenesis [97].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One gene, DUSP1, is a major negative regulator of MAP kinase signaling that is decreased in MASLD patients and shows increased expression following gastrectomy linked to the amelioration of liver disease [94]. The second gene, SIRT1, protects cells from metabolic stress and steatotic liver disease by deacetylating proteins associated with lipid metabolism [95, 96]. A third inhibited late upstream regulator, CITED2, is a transcriptional co-activator that promotes hepatic gluconeogenesis [97].…”
Section: Resultsmentioning
confidence: 99%
“…Upstream regulators specifically activated at the 2 wk TCPOBOP time point included: STAT1, which promotes MASH [88,89]; MYD88, which induces liver inflammation and M2 macrophage polarization [90,91]; and several NFKB inflammatory pathway regulators [93]. Late upstream regulators, including the MASLD protective factors DUSP1 [94] and SIRT1 [95,96], were predicted to be inhibited by TCPOBOP exposure, and may thus contribute to steatotic liver disease progression. Macrophage activation and reactive oxygen species production and metabolism, and to a lesser extent inflammation, were identified as Disease and Bio Functions strongly enriched after 2 wk but not after 1 d TCPOBOP exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic fat deposition is characterized by the accumulation of TG within hepatocytes ( 42 ). Previous studies have shown an association between hepatic fat deposition and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, when the circadian Clock component Bmal1 is disrupted, the subsequent endocrine adaptation has an important impact on insulin sensitivity, liver disease, and the metabolic syndrome [ 11 , 12 ]. The rhythmic expression of Bmal1 and Clock as master Clock-controlled genes are significantly involved in lipid metabolism and fatty liver disorder [ 13 ].…”
Section: Introductionmentioning
confidence: 99%